1985
DOI: 10.1080/00071668508416801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary copper on litter microbial population and broiler performance

Abstract: Proprietary broiler diets, containing added copper (125 mg/kg) as sulphate, were fed to broilers in 4 trials (32 pens each) over a one year period without a change of litter. Mould counts in the litter of pens containing birds fed the standard diets decreased to 2 X 10(3) propagules per g in trial 4. Those in the pens with birds fed the diets containing supplemental copper decreased to 6 X 10(2) propagules per g. Litter bacterial counts (10(7) organisms/g) were not affected by dietary copper. Litter copper con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…High levels of Cu have also been used in broiler diets because of increases noted in production, such as improved weight gains. Johnson et al (1985) found that diets containing 125 mg Cu kg −1 (as copper sulfate) resulted in improved weight gains. They found that the mold counts in litter of birds grown with additional Cu were 95% lower than that of the control diet and suggested that high levels of Cu in the litter (600 mg Cu kg −1 ) resulted in reductions in mold, which was the cause of improved weight gains.…”
mentioning
confidence: 99%
“…High levels of Cu have also been used in broiler diets because of increases noted in production, such as improved weight gains. Johnson et al (1985) found that diets containing 125 mg Cu kg −1 (as copper sulfate) resulted in improved weight gains. They found that the mold counts in litter of birds grown with additional Cu were 95% lower than that of the control diet and suggested that high levels of Cu in the litter (600 mg Cu kg −1 ) resulted in reductions in mold, which was the cause of improved weight gains.…”
mentioning
confidence: 99%
“…Various elements are added to poultry rations, such as As, Co, Cu, Fe, Mn, Se, and Zn (Moore, 1998). Copper sulfate is often added to the diet of broilers to increase weight gain and avoid diseases (Johnson et al, 1985). Other elements are added to feed so that young birds can tolerate various stresses under high‐population conditions in the house (Tufft and Nockels, 1991).…”
mentioning
confidence: 99%
“…Johnson et al (1985) tested the effect of 125 mg Cu kg -1 (cupric sulfate) in broiler chicken diet on the performance and the concentration of this mineral in the litter, and its effects on the microflora in four successive trials carried out during a 12-month period, without changing the bedding. The authors did not find differences in bird growth and feed conversion efficiency for the first and second trials.…”
Section: Resultsmentioning
confidence: 99%